2020
DOI: 10.6008/cbpc2179-6858.2021.001.0055
|View full text |Cite
|
Sign up to set email alerts
|

Trends in scientific publication on ethnozoology: Brazil’s highlight in international science

Abstract: We investigate the trends of the scientific publication on ethno-zoological studies by using the word 'Ethnozoology' in the Web of Science database. We associate the number of published documents with the timescale, publication sources, countries and affiliations, authors, and most frequent words in the publications. We found 177 documents published between 1967 and 2019, with a significant increase over the last 10 years. The Journal of Ethnobiology and Ethnomedicine, Journal of Ethnopharmacology, Indian Jour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The growing in articles on bushmeat consumption and trade observed in recent years in our search is not surprising. Considering that in recent decades we have seen the insertion of new graduate programs in the country, the entry of new researchers, an increase in the number of newspapers that will certainly increase the Ethnozoological publications in the Brazil [ 41 , 56 , 58 , 59 ]. Also, the increase of researchers with specific training in the fields of Ethnobiology and Ethnozoology and the existence of links between Brazilian researchers and from other international countries make Brazil a reference in this field in the Latin American context [ 56 , 58 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…The growing in articles on bushmeat consumption and trade observed in recent years in our search is not surprising. Considering that in recent decades we have seen the insertion of new graduate programs in the country, the entry of new researchers, an increase in the number of newspapers that will certainly increase the Ethnozoological publications in the Brazil [ 41 , 56 , 58 , 59 ]. Also, the increase of researchers with specific training in the fields of Ethnobiology and Ethnozoology and the existence of links between Brazilian researchers and from other international countries make Brazil a reference in this field in the Latin American context [ 56 , 58 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Scientometrics examines aspects of information and communication using quantitative and qualitative indicators to study scientific production (Santos & Kobashi 2009). This allows evaluate the performance or trends in knowledge production between researchers, groups, universities or nations (Oliveira & Lopes 2021). For example, the scientometric analysis may include gender, academic formation, or academic experience.…”
Section: Introductionmentioning
confidence: 99%
“…The causes of this gap are diverse, such as the decrease in the time invested in research by females due to motherhood and socially imposed gender roles, less financial support for research (Abramo et al 2009, Borsuk et al 2009, Larivière et al 2013, Lopes & Lopes 2022, Prpiû 2002, or socio-historical causes due to the hegemonic structure of scientific production (Krause 2016). Although studies have shown the gender gap expressed in the number of researchers and project funding (Ferrari et al 2018, Oliveira et al 2021, Salerno et al 2019, Zandonà 2022, little is known about the differences in scientific production between males and females in the Biodiversity and Ecology research (Mcmanus et al 2020, Zandonà 2022.…”
Section: Introductionmentioning
confidence: 99%